The Significance of Mall Roles in Accelerating Halal Certification Policies: A Case Study of Plaza Balikpapan Mall - Abdul Mujib Syadzali; Muhammad Uswah Pawara (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
This research describes the application and strategy of Mall Plaza Balikpapan in accelerating the implementation of Halal policy in Indonesia. The research method used is qualitative by using data collection through interview, observation and documentation study. Then the data analysis uses descriptive analysis to explain the applied policies and strategies regarding halal issues at Plaza Balikpapan Mall. The results found in this research that the mall is very serious in ensuring tenants, retailers or tenants to follow the halal policy in the form of mandatory. Then the conclusion of the field findings at Mal Plaza Balikpapan Mall, the mall becomes a mediator of the halal policy, proven through mall circulars to each of their tenants, balanced by taking a persuasive approach, by directly visiting each tenant to understand and follow the halal policy. The mall then educates its tenants with the help of the Ministry of Religious Affairs Balikpapan and the Campus of The Institute of Technology Kalimantan. As another result of the findings in the field, Mall Plaza Balikpapan mediates education and promotion of halal value chain in collaboration with Bank Indonesia Balikpapan by organizing Festival Pekan Syariah Nusantara. In the festival, the mall held a bazaar of creative producers of halal food products, this is an event for the mall to promote the halal industry. Then, regarding education in the mall festival, the head of the Halal Registration and Certification Centre of BPJPH and the Deputy Director of Sharia Business Incubation at KNEKS at Plaza Balikpapan Mall.